Unity 2021 Cookbook - Fourth Edition - Smith, Matt; Ferns, Shaun; Gregan, Chris (Packt Publishing, 2021)
Discover practical solutions to everyday problems in developing 2D and 3D games and AR/VR applications using the latest features of Unity 2021 Key Features Discover the latest features of Unity 2021 in this updated fourth edition including coverage of AR/VR development Focus on 2D and 2D character development with Unity GameKits Learn powerful techniques and expert best practices in building 3D objects, textures, and materials Book Description Unity is the most widely used game development platform worldwide. Available for Windows, macOS, and Linux, Unity is a powerful and easy-to-use one-stop solution for creating games for mobile, web, desktop and games consoles. This fourth edition of the Unity Cookbook series is updated with the latest features of Unity 2021 and modern game development practices, and will help you address common hurdles faced by Unity game developers. The cookbook helps you work through a wide variety of recipes relating to the essential features of the Unity game engine. You will get to grips with shaders and Shader Graph, before exploring animation features to enhance your skills in building games. As you progress, you will gain insights into Unity's latest editor which will help you in laying out scenes, tweaking existing apps, and building custom tools for augmented reality and virtual reality (AR/VR) experiences. The book also guides you through many Unity C# gameplay scripting techniques, teaching you how to communicate with database-driven websites and process XML and JSON data files. By the end of this Unity book, you will have gained a comprehensive understanding of Unity game development and built your development skills. What you will learn Discover how to add core game features to your projects with C# scripting Create powerful and stylish UI with Unity's UI system, including power bars, radars, and button-driven scene changes Work with essential audio features, including background music and sound effects Discover Cinemachine in Unity to intelligently control camera movements Add visual effects such as smoke and explosions by creating and customizing particle systems Understand how to build your own Shaders with the Shader Graph tool Who this book is for This book is for existing Unity developers who want to explore a wide range of Unity scripting and multimedia features using ready-to-use recipes in the Unity engine. Programmers looking to explore multimedia features will also find this book useful. Beginner- ...